Paid Educational Leave in Europe: Its Implications for Canada - Jain, Hem (Relations industrielles / Industrial Relations, 1978)
This article reviews the increased educational opportunities provided to workers in a number of Western countries, Belgium, France, the Federal Republic of Germany, Sweden and the United Kingdom, through national, regional or local legislation or through collective bargaining and other private mechanisms. An attempt has also been made to analyze and compare the Belgian and the French experiences with regard to P.E.L. Finally, this article examines the relevante of the European experience in respect at P.E.L. for policy makers and other interested parties in Canada.